The Process of Uterine Involution with Postpartum Exercise of Maternal Postpartum - Metha Fahriani; Dewi Aprilia Ningsih; Asih Kurnia; Violita Siska Mutiara (JURNAL KEBIDANAN, 2020)
The purpose of this study was to determine the effect of postpartum exercise on a uteri involution maternal postpartum look for decreasing of fundal height on maternal postpartum. This study was a pre-experimental study using a Static Group Comparison design. The population was a postpartum mother who gave birth normally. Sampling technique by accidental sampling as 30 people, where 15 people in the intervention group and 15 people in the control group. Data was conducted observation used pelvimetry. The intervention group did postpartum exercise and did not do, then measured the fundal height 6 hours postpartum, day 3, day 6, and day 10. Data were analyzed using independent sample t-test and Two-sample Kolmogorov- Smirnov Test. The result of this research got a mean of the fundal height of 6-hour postpartum in intervention group 13,00 cm ±1,000 cm and13,27 cm ± 1,033 cm in the control group. Mean of fundal height third day in the intervention group 7,87 cm ±0,743 cm and 9,33 cm ± 0,900 cm in the control group. Mean of fundal height sixth day in intervention group 4,07 cm ±0,704 cm and 5,60 ± 1,121 cm in control group. While mean of fundal height tenth day in intervention group 0,33 cm ± 0,488 cm and 1,20 cm ± 0,676 cm in control group. There was a significant difference in the decrease of fundal height between the two groups. From the results of this study, it can be concluded that the postpartum exercise has an effect on the decrease of fundal height.